Examining Thread Vulnerability analysis using fault-injection - (:unkn) unknown (IEEE Computer Society, 2013)
With the scale down of transistor sizes and higher frequencies with low power modes in modern architectures, the chip components become more susceptible to transient errors. Concurrently, multicore machines are replacing traditional single-core machines in most application domains. Thread Vulnerability Factor (TVF) is a metric to evaluate relative soft error vulnerability of multithreaded applications running on multicore architectures. It makes possible vulnerability analysis of parallel programs by providing comparisons between them. In this work, we design a simulation-based fault-injection framework to evaluate soft error vulnerability of parallel applications and perform a validation study to evaluate parallel program vulnerability. The results of the simulation-based fault injection framework is compared with the results based on TVF analysis. Our results demonstrate that TVF provides an efficient vulnerability analysis by having the same ordering and similar vulnerability rates with fault-injection results for a set of multithreaded applications. © 2013 IEEE.